Impact of amine functionality on the selective CO2/CH4 adsorption behavior of porous covalent triazine adsorbent - Mukhtar, A. (Elsevier B.V., 2020)
In this paper, a porous covalent triazine based framework (CTF) was prepared from cyanuric chloride and 1,4-Phenylenediamine via catalyst-free condensation polymerization. The CTF was post-synthetically functionalized (CTF-NH) with monoethanolamine (MEA). The structural and texture properties were investigated by solubility, FESEM, EDX, Mapping, FTIR, PXRD, TGA/DTG, BET analysis, water and chemical stability, and selective CO2/CH4 adsorption behavior. The results showed the surface area loss from 20.6118 m2/g to 18.0647 m2/g due to modification resulting in CO2 uptake capacity enhancement of 41.9 and also improvement in the CO2/CH4 selectivity. The polymers were found to be amorphous and highly thermally stable. Furthermore, the insoluble nature of both polymer in common solvents dictates their robust nature, highly hygroscopic and found highly stable acid and base over one week while sustaining surface area and adsorption capacity. The results present in this work indicate the significance of microporous COPs with amine-functionalized pores towards the selective CO2/CH4 separation. Â© 2020 Elsevier B.V.